Metacognitive Strategies of EFL Students in Reading Online Academic Text - Munawaroh, Kholilatul; Hamiddin, Hamiddin; Widowati, Diah Retno (Prominent, 2025)
This study aimed to identify metacognitive strategies that EFL students  may employ when reading online academic text. Seventy-seven of seventh-semester English Education Department students from a private institution in Malang participated in this mixed-methods study. Since they were finishing their theses, these students were chosen considering that they were EFL students who frequently read academic text online. As the research’s instruments, the Online Survey of Reading Strategies (OSORS) and interviews, data were acquired. Microsoft Excel was used to evaluate the questionnaire data, while content analysis was used to examine the interview data. The findings from questionnaire indicated that problem-solving strategies are the ones that EFL students apply the most when reading academic text online. Moreover, each student uses metacognitive strategies in a distinctive manner, according to the interviews with the three students. The strategies assist EFL students understand academic text in online settings and they are useful in online learning environments. The results show how crucial reading strategies especially for academic text online. Future research on this topic is anticipated to include an inquiry with a wider range of participants and across competency levels.